Green it Parvasiveness in Business Activities Towards Environmental Conservation - Nelwan, Melinda Lydia (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Every company, partucularly IT business is facing a challenge in performing business practices that complied with the enviromental conservation. As a response, IT sector had fostered an initiatif identified as ‘Green IT’ which is a practice of designing, manufacturing, using and disposing of IT equipments with less damage to the enviroment. Implementing green IT practices will assist a company to respond to its moral abligation in preserving the environment and abiding in government regulation. Nevertheless, a company has to consider some challenges in praticing green IT such as investing in IT hardware and infrastucture without sacrificing its profitability. At last, the green IT initiatives will be beneficial for the company in creating competitive advantages and to be able to sustain its business performance.